Citra Perempuan pada Iklan KPK 2024 Cegah Nyokap dari Suap; Analisis Wacana Kritis Kajian Sara Mills - Uswatun Khasanah, Siti; Setiyawan, Radius (J-SES : Journal of Science, Education and Studies, 2024)
The importance of this research is to dig deeper into how advertising plays an active role in representing gender and influencing people’s perceptions. This research aims to find out what image is formed of woman through the KPK advertisement “Prevent Nyokap from Bribery” ahead of the 2024 election using critical discourse analysis of Sara Mills theory. This research is qualitative research with descriptive methods. This research data is in the form of analyzing data sourced from KPK advertisements in the form of images from the official website kpk.go.id. Data was collected using listening techniques, then analyzed by describing and recording the data that had been collected. The focus of this research is to see how women are represented in advertisements through thir existing positions. Based on the analysis and research that has been carried out, it was found that the position of men as subjects and woman as objects in these advertisements. The final results of the research show that the image presented in this advertisements is a negative image of woman, namely that woman tend not to think critically in choosing leaders, labelling them materealistic as well as being extravagant.